Cracking Go. - Feng-Hsiung Hsu (IEEE spectrum)
Many of the early computer-chess researchers hailed from the fields of psychology or artificial intelligence and believed that chess programs should mimic human thinking. Specifically, they wanted computers to examine only playing sequences that were meaningful according to some human reasoning process. In computer chess this policy, known as selective search, never really made progress. The reason is that humans are extremely good at recognizing patterns; it is one of the things that we do best. The article focuses on weiqi, an ancient Chinese board game, better known in the West by the Japanese name of Go, whose combinatorial complexity is many orders of magnitude greater than that of chess. Go is played on a board crisscrossed by 19 vertical and 19 horizontal lines whose 361 points of intersection constitute the playing field. The object is to conquer those intersection points.